THU0658 WHO IS AT RISK FOR PERSISTENT FATIGUE IN THE FIRST YEAR OF RA? CHARACTERISTICS OF PATIENTS WITH PERSISTENT FATIGUE IN THE FIRST YEAR BY SEX IN THE CANADIAN EARLY ARTHRITIS COHORT (CATCH). (June 2019) - Bartlett, Susan J.; Schieir, Orit; Valois, Marie-France; Pope, Janet; Bessette, Louis; Hitchon, Carol; Thorne, Carter; Tin, Diane; Hazlewood, Glen; Boire, Gilles; Keystone, Edward; Bykerk, Vivian
Abstract : Background: While treat-to-target strategies can dramatically reduce RA inflammation, persistent fatigue is present in up to half of RA patients, and is an important unmet need. Proposed underlying causes include RA disease, cognitive/emotional/behavioral (CEB), and personal (health) factors. Objectives: To identify risk factors for persistent fatigue at 12-months in men and women with ERA on immunomodulatory therapies. Methods: Data were from patients enrolled in the Canadian Early Arthritis Cohort (CATCH) between 01-2007 and 03-2017 who met 1987 or 2010 ACR/EULAR RA criteria, had active disease treated with DMARDS, and had complete data on DAS28, BMI, and fatigue severity (0-10) over 12-months. Persistent fatigue, was defined as fatigue >4 at baseline with <20% improvement at 12 months. Multivariable logistic regression was used to identify RA disease, CEB, and personal/health factors associated with persistent fatigue. Results: Patients were mostly white (81%), female (71%), with a mean (SD) age of 54 (15), symptom duration of 6 (3) months, and BMI of 28.0 (6.1); 32% were obese (BMI≥30). Women were generally younger, better educated, seropositive, and had greater disability, fatigue, depressive symptoms, and major stress in the past year (p<.05). 21% of women and 19% of men reported persistent fatigue. In multivariable regression that included all Table 1 variables, predictors of persistent fatigue in women were obesity (OR 1.7; 95% CI 1.1, 2.6), initial steroid use (OR 1.7; 95% CI 1.1, 2.7), seronegativity (OR 0.6; 95% CI 0.4, 1.0) and poor sleep (OR 1.1; 95% CI 1.0, 1.2). Obesity was the only significant predictor in men and was assoicated with a 2.4 times higher odds (95% CI 1.1, 5.1) of persistent fatigue at 1 yr. Other sociodemographic, RA characteristic, CEB and personal/health factors were not associated with persistent fatigue in either sex in multivariable models. Conclusion: Obesity is common in ERA and a major determinant of persistent fatigue in women and men. In obese RA patients on guideline-based treatment, lifestyle interventions targeting weight loss may play an important role in reducing persistent fatigue that does not improve with RA treatment. Disclosure of Interests: Susan J. Bartlett Consultant for: Pfizer, UCB, Lilly, Novartis, Merck, Jansen, Abbvie, Orit Schieir: None declared, Marie-France Valois: None declared, Janet Pope Consultant for: Eli Lilly and Company, Louis Bessette Grant/research support from: Amgen, BMS, Janssen, Roche, UCB, AbbVie, Pfizer, Merck, Celgene, Sanofi, Lilly, Novartis, Consultant for: Amgen, BMS, Janssen, Roche, UCB, AbbVie, Pfizer, Merck, Celgene, Sanofi, Lilly, Novartis, Speakers bureau: Amgen, BMS, Janssen, Roche, UCB, AbbVie, Pfizer, Merck, Celgene, Sanofi, Lilly, Novartis, CArol Hitchon Grant/research support from: Pfizer, UCB (unrelated studies), Carter Thorne Grant/research support from: Investigator-initiated studies: Amgen, Pfizer. RCTs: Abbvie, Celgene, CaREBiodam, Novartis, Pfizer, Consultant for: Advisory board: Abbvie, Amgen, Celgene, Lilly, Medexus/Medac, Merck, Novartis, Pfizer, Sanofi. Consultant: Abbvie, Centocor, Janssen, Lilly, Medexus/Medac, Pfizer, Speakers bureau: Medexus/Medac, Diane Tin: None declared, Glen Hazlewood: None declared, Gilles Boire Grant/research support from: Investigator-initiated studies: Amgen, Abbvie, BMS, Eli Lilly, Merck, Novartis, Pfizer, Consultant for: Advisory boards: Amgen, BMS, Celgene, Eli Lilly, Pfizer, Speakers bureau: Merck, BMS, Pfizer, Edward Keystone Grant/research support from: AbbVie, Amgen, Bristol-Myers Squibb, F. Hoffmann-La Roche Inc, Gilead, Janssen Inc, Lilly Pharmaceuticals, Pfizer Pharmaceuticals, Sanofi-Aventis, Consultant for: AbbVie, Amgen, AstraZeneca Pharma, Biotest, Bristol-Myers Squibb Company, Celltrion, Crescendo Bioscience, F. Hoffmann-La Roche Inc, Genentech Inc, Gilead, Janssen Inc, Lilly Pharmaceuticals, Merck, Pfizer Pharmaceuticals, Sandoz, UCB., Speakers bureau: Amgen, AbbVie, Bristol-Myers Squibb Canada, F. Hoffmann-La Roche Inc., Janssen Inc., Merck, Pfizer Pharmaceuticals, Sanofi Genzyme, UCB, Vivian Bykerk Grant/research support from: Mallinckrodt, BMS, Crescendo Biosciences, Sanofi/Regeneron., Consultant for: Amgen, Pfizer, UCB, Scipher, Sanofi/Genzyme/Regeneron